PEMANFAATAN BLANGKO OPINI UNTUK MENINGKATKAN PARTISIPASI MAHASISWA DALAM PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION - Agus Budi Santosa (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2014)
Learning process is the logical essence of college education in affectingthe quality of output. Infact, the implementation of teaching and learning process in the classroom are faced on the problems that hinder the succes of the learning process. The troubling problem that occurs is the student low participation, which tends to just sit down, be quiet, and just listen without giving a response that is relevant to the learning process takes place.        The implementation Group Investigation of cooperative learning model wasdifficult to reach expectations. Researchers tried to use opinion form to solve the low of students participation on the discussion process of teaching and learning in STKIP PGRI Trenggalek.        The design of this research is classroom action research (Kemmis and Taggart design) that consist of three cycles, using constructivist approach with qualitative data. Data were collected by the method of observation, interviews and giving assignment. Then, it is analyzed descriptively (datareduction, datapresentation, and inference).         The results of data analysis showed that the use of opinion form can improve students’ participation in cooperative learning on the subject of Belajar Pembelajaran, students are able to changetheir habits that tend to be passive to be students who has a willing to study hard and aware how to pose themselves and take part actively especially in delivering question, giving opinion and responsible to their duties of becoming students. The use of opinion form facilitate lecturerto motivate students to actively participate in the learning process because they are not only get an invitation and verbal motivation but also acts directly on the work.